Monazite as a monitor for melt‐rock interaction during cooling and exhumation. (15th February 2019) - Prent, Alexander M.; Beinlich, Andreas; Morrissey, Laura J.; Raimondo, Tom; Clark, Chris; Putnis, Andrew
Abstract: Granulite facies cordierite–garnet–biotite gneisses from the southeastern Reynolds Range, central Australia, contain both orthopyroxene‐bearing and orthopyroxene‐free quartzofeldspathic leucosomes. Mineral reaction microstructures at the interface of gneiss and leucosome observed in outcrop and petrographically, reflect melt‐rock interaction during crystallization. Accessory monazite, susceptible to fluid alteration, dissolution and recrystallization at high temperature, is tested for its applicability to constrain the chemical and P–T –time evolution of melt‐rock reactions during crystallization upon cooling. Bulk rock geochemistry and phase equilibria modelling constrain peak pressure and temperature conditions to 6.5–7.5 kbar and ~850°C, and U – Pb geochronology constrains the timing of monazite crystallization to 1.55 Ga, coeval with the Chewings Orogeny. Modelling predicts the presence of up to 15 vol.% melt at peak metamorphic conditions. Upon cooling below 800°C, melt extraction and in situ crystallization of melt decrease the melt volume to less than 7%, at which time it becomes entrapped and melt pockets induce replacement reactions in the adjacent host rock. Replacement reactions of garnet, orthopyroxene and K‐feldspar liberate Y, REE, Eu and U in addition to Mg, Fe, Al, Si and K. We demonstrate that distinguishing between monazite varieties solely on the basis of U–Pb ages cannot solve the chronological order of events in this study, nor does it tie monazite to the evolution of melt or stability of rock‐forming minerals. Rather, we argue that analyses of various internal monazite textures, their composition and overprinting relations allow us to identify the chronology of events following the metamorphic peak. We infer that retrograde reactions involving garnet, orthopyroxene and K‐feldspar can be attributed to melt‐rock interaction subsequent to partial melting, which is reflected in the development of compositionally distinct monazite textural domains. Internal monazite textures and their composition are consistent with dissolution and precipitation reactions induced by a high‐ T melt. Monazite rims enriched in Y, HREE, Eu and U indicate an increased availability of these elements, consistent with the breakdown of orthopyroxene, garnet and K‐feldspar observed petrographically. Our study indicates that compositional and textural analysis of monazite in relation to major rock‐forming minerals can be used to infer the post‐peak chemical evolution of partial melts during high‐ to ultrahigh‐temperature metamorphism.